Processing and managing complex OWL data - Abuazab, Hussam; Elci, Atilla (Insticc-Inst Syst Technologies Information Control & Communication, 2008)
In this paper we introduce new OWL class sets that can be obtained through and manipulated by Boolean operators. The need for new class sets come in order to process and manage complex OWL data, and to improve the expressive power of OWL language. A particular need for such sets arises in processing complex data involved in ontology for human disease which is being developed. The class sets introduced in this paper include the definition of minusOf, De Morgan's Law, and Auxiliary Identity properties.
4th International Conference on Web Information Systems and Technologies -- MAY 04-07, 2008 -- Funchal, PORTUGAL
Keywords: OWL class sets; DeMorgan's Law; minusOf; Auxiliary Identity